Navigating the challenges of studying abroad: a culturally responsive alumni mentorship (CRAM) approach for Indonesian freshmen at Asia University Taiwan - Andi Azhar; Risda Yulianti; Ade Tiara Yulinda (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This paper examines a community engagement initiative employing Culturally Responsive Alumni Mentorship (CRAM) to support Indonesian freshmen at Asia University, Taiwan. Recognizing the challenges of cultural transition and financial constraints, this initiative, led by an Indonesian alumnus, provided a culturally relevant platform for students to thrive. A sharing and discussion session held on September 10th addressed key areas like academic strategies, cultural adjustment, and financial management. CRAM emphasizes leveraging alumni experiences to offer culturally specific guidance. The session fostered a sense of community and facilitated knowledge sharing, leading to positive outcomes such as enhanced cultural awareness, improved confidence, and reduced anxiety. This study highlights the potential of CRAM in empowering international students to navigate the complexities of studying abroad and achieve academic success